The 50–100 pc scale parent stellar populations of Type II supernovae and limitations of single star evolution models. Issue 4 (12th October 2019) - Schady, P; Eldridge, J J; Anderson, J; Chen, T-W; Galbany, L; Kuncarayakti, H; Xiao, L
ABSTRACT: There is observational evidence of a dearth in core-collapse supernova (ccSN) explosions from stars with zero-age main-sequence (ZAMS) mass M 0 ≈ 17–30M⊙, referred to as the 'red supergiant problem'. However, simulations now predict that above 20 M⊙ we should indeed only expect stars within certain pockets of M 0 to produce a visible SN explosion. Validating these predictions requires large numbers of ccSNe of different types with measured M 0, which is challenging. In this paper, we explore the reliability of using host galaxy emission lines and the H α equivalent width to constrain the age, and thus the M 0 of ccSNe progenitors. We use Binary Population and Spectral Synthesis models to infer a stellar population age from MUSE observations of the ionized gas properties and H α EW at the location of eleven ccSNe with reliable M 0 measurements. Comparing our results to published M 0 values, we find that models that do not consider binary systems yield stellar ages that are systematically too young (thus M 0 too large), whereas accounting for binary system interactions typically overpredict the stellar age (thus underpredict M 0 ). Taking into account the effects of photon leakage bring our M 0 estimates in much closer agreement with expectations. These results highlight the need for careful modelling of diffuse environments, such as are present in the vicinity of Type II SNe, before ionized emission line spectra can be used as reliable tracers of progenitor stellar age.